2018
DOI: 10.1080/17445647.2018.1530154
|View full text |Cite
|
Sign up to set email alerts
|

Valley network morphology in the greater Meridiani Planum region, Mars

Abstract: The Greater Meridiani Planum region on Mars is a key locale for a diverse range of fluvial landforms. Valley networks in this region have a range of geomorphologic styles that include negative relief, positive relief, or some combination of both along their lengths. Using highresolution ∼5-6 m/pixel orbital images in ArcGIS Desktop software, we mapped previously under-recognized fine-scale valley networks within the Greater Meridiani Planum region and recorded their geomorphic characteristics as feature attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Numerous branching and curvilinear ridge systems are exposed at the surface throughout Arabia Terra. (Figures , , and S1; e.g., Chuang & Williams, ; Davis et al, ; Williams et al, ; note the descriptions in this section are also applicable to those in section ). These ridges are generally contiguous or semicontiguous for tens of kilometers, with the longest observed contiguous segment being ~200 km in length (six additional segments are greater than 100 km; Table S2).…”
Section: Observationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Numerous branching and curvilinear ridge systems are exposed at the surface throughout Arabia Terra. (Figures , , and S1; e.g., Chuang & Williams, ; Davis et al, ; Williams et al, ; note the descriptions in this section are also applicable to those in section ). These ridges are generally contiguous or semicontiguous for tens of kilometers, with the longest observed contiguous segment being ~200 km in length (six additional segments are greater than 100 km; Table S2).…”
Section: Observationsmentioning
confidence: 97%
“…Although valley networks are generally absent in southwest Arabia Terra (Alemanno et al, 2018;Hynek et al, 2010), several large, regionally integrated erosional valley networks and intravalley basins traverse the central region of Arabia Terra (e.g., Naktong, Scamander Vallis), interpreted to have formed near the Noachian/Hesperian boundary (Fassett & Head, 2008a;Goudge et al, 2012;Irwin et al, 2005). Underlying the etched units is a network of branching and sinuous ridges, which comprise the remains of fluvial channel deposits (Chuang & Williams, 2018;Davis et al, 2016;Williams et al, 2018) and are predominantly found on middle to late Noachian age terrains (Hynek & Di Achille, 2017).…”
Section: Geology Of Arabia Terramentioning
confidence: 99%
See 1 more Smart Citation